The blackcoat's daughter [videorecording (DVD)] - Perkins, Oz, 1974-; Roberts, Emma, 1991-; Shipka, Kiernan, 1999-; Boynton, Lucy; Holly, Lauren (Lions Gate Entertainment, 2017)
Beautiful and haunted Joan makes a bloody and determined pilgrimage across a frozen landscape toward a prestigious all-girls prep school, where Rose and Kat find themselves stranded after their parents mysteriously fail to retrieve them for winter break. As Joan gets closer, Rose watches in horror while Kat suffers terrifying visions and becomes possessed by an unseen force.